Science and religion : Christian and Muslim perspectives : a record of the eighth Building Bridges Seminar convened by the Archbishop of Canterbury, Bahçeşehir University, Istanbul, 16-18 June 2009 - Marshall, David, 1963- (UPCC book collections on Project MUSE., 2012)
Science and Religion is a record of the 2009 Building Bridges seminar, a dialogue between leading Christian and Muslim scholars convened annually by the Archbishop of Canterbury. The essays in this volume explore how both faith traditions have approached the interface between science and religion and throw light on the ongoing challenges posed by this issue today. The volume includes a selection of relevant texts together with commentary that illuminates the scriptures, the ideas of key religious thinkers, and also the legacy of Charles Darwin.